Single-cell and spatial analyses reveal a tradeoff between murine mammary proliferation and lineage programs associated with endocrine cues - Gray, G. Kenneth; Girnius, Nomeda; Kuiken, Hendrik J.; Henstridge, Aylin Z.; Brugge, Joan S. (Cell reports (Cambridge), 2023)
Although distinct epithelial cell types have been distinguished in glandular tissues such as the mammary gland, the extent of heterogeneity within each cell type and the degree of endocrine control of this diversity across development are incompletely understood. By combining mass cytometry and cyclic immunofluorescence, we define a rich array of murine mammary epithelial cell subtypes associated with puberty, the estrous cycle, and sex. These subtypes are differentially proliferative and spatially segregate distinctly in adult versus pubescent glands. Further, we identify systematic suppression of lineage programs at the protein and RNA levels as a common feature of mammary epithelial expansion during puberty, the estrous cycle, and gestation and uncover a pervasive enrichment of ribosomal protein genes in luminal cells elicited specifically during progesterone-dominant expansionary periods. Collectively, these data expand our knowledge of murine mammary epithelial heterogeneity and connect endocrine-driven epithelial expansion with lineage suppression. [Display omitted] •Single-cell analyses identify murine mammary epithelial subtypes•Spatially distinct subtypes are associated with puberty and the estrous cycle•Lineage suppression accompanies proliferative expansion Gray et al. generate a protein and spatial atlas of the murine mammary gland. Distinct epithelial subtypes are associated with puberty, the estrous cycle, and male tissue. Suppression of epithelial lineage programs accompanies endocrine-driven proliferative expansion and de novo structure formation. Progesterone signaling is connected to ribosomal protein gene transcription.